Dynamic Weighted and Heat-map Integrated Scalable Information Path-planning Algorithm - Bi, Shuhui; Li, Zhihao; Xu, Yuan; Wang, Lei (EAI endorsed transactions on scalable information systems, 2023)
We, the publisher, removed Mackenzie Brown from the article: Bi, S., Li, Z., Brown, M., Xu, Y., & Wang, L. (2022). Dynamic Weighted and Heat-map Integrated Scalable Information Path-planning Algorithm. EAI Endorsed Transactions on Scalable Information Systems, 10(2), e5. https://doi.org/10.4108/eetsis.v9i5.1567 after being notified by the Research Integrity and Governance Adviser of Edith Cowan University, that the author has never been affiliated with that institution. All the authors were informed about this fact and we did not receive any explanation about it. It was not clarified whether this was an "involuntary mistake" or a "false author." Following the COPE guidelines, Mackenzie Brown was REMOVED from this article because of “Potentially fake academic affiliation”.